Cross-Gendering the Racial Memory - Marlon B. Ross (Transatlantica)
When Ernest Gaines chooses a woman as the individual subject for collective memorialization and the ideal medium of racial memory in his 1971 novel, The Autobiography of Miss Jane Pittman, he participates in a significant but overlooked genre of black masculine discourse, the composition of black authorship as historical/national authority through the voice and viewpoint of a female protagonist. This cross-gendering of the racial imaginary, introjecting a male vision of racial collectivity and history through a female’s frame of reference, though not exactly a form of cross-dressing, can be usefully analyzed as such. Erecting a feminine monument to emblematize and materialize highly abstract notions like nationhood, justice, peace, warfare, virtue, democracy, pro/creativity, and truth has a long history in many cultures across the globe. It is a long-standing practice within many patriarchal cultures, in other words, to project highly abstract masculine visions of established power onto a female form, draped in feminine attire. Whether this occurs metaphorically, as in the case of gendering the nation-state as feminine (Britannia for the United Kingdom, Columbia for the United States, St. Joan for France, etc.), or through more literal iconography, such as the Statue of Liberty, the feminine form serves to purify, emblematize, and collectivize—and thus to transcendentalize—concepts of rightful dis/empowerment that are otherwise fraught with cultural-historical strife. The static nature of such imagery distances us from the contentiousness of the act of cross-gendering that occurs ideologically in the enunciation or re-erection of patriarchal power through an objectified, if celebrated, feminine icon.We can find evidence of this conventionally patriarchal kind of feminine iconography in black cultural practice.  For instance, in black nationalist discourse of the 1960s and ’70s (whether in the Black Power movement in the United States or the post-colonial movements in the West Indies and Africa), there is a tendency to emblematize the rising black nation as a fecund black mother, frequently figured more transcendently as “Mother Africa” herself, even as the battle for and leadership of these emerging nations is assumed to be the purview of militant big men. Ironically, to index the greatness of the emerging nation, and the bigness of the male freedom fighters and founders, both figuratively and materially the female icon must be giganticized, making her a presence so massive as to become a queer she-male—masculine in size and intent, feminine in spirit and form. In European-American iconography, there is a drive to materialize this gigantic feminine figure not only by super-sizing her but also by casting her in the hardest stones—again the Statue of Liberty providing a perfect instance. Lacking the economic resources for such a luxury of patriarchal imagination, black nationalist practice most frequently resorts to more figurative embodiments of the gigantic feminine in art, poetry, song, and dance.Gaines’s gigantic female who voices and embodies black American epochal and epical history, Miss Jane Pittman, is cast as novel and film (1974) at the height of the black nationalist moment, when metaphorical she/males emblematizing the masculine heroism of black nation-building are proliferating all over the place in black popular culture. This paper analyzes Miss Jane Pittman in this historical context of the black nationalist gigantic female icon. I argue that while Gaines draws on this black nationalist image as context and subtext, he diverts attention away from this militant and often violent black nationalist iconography of cross-gendering to figure instead a strong, enduring black woman as a pacifying emblem of cross-racial American nation-building. Opting to follow the lead of other black male cross-gendering writers—most notably James Weldon Johnson, W. E. B. Du Bois, Walter White, and Wallace Thurman—Gaines erects Miss Jane as a she/male icon who prophesies the integrated, interracial, harmonious United States nation that emerges ironically out of black folk’s capacity to endure and transcend an entrenched history of state-endorsed racial violence and abjection. Gaines chooses a woman as his medium/subject both to envelope the image of the gigantic black feminine as black nationalist icon and to counter that image in favor of a conscientious black nation within a bloody white nation, the black (wo)man as the purifying conscience of the historically compromised American nation-state. On the one hand, Gaines’s iconography has the benefit of disturbing and subverting the normatively masculine stance of black nationalism by figuring a she/male whose cross-gendering is less aggressively patriarchal in size and intent, more ambivalently feminine in spirit and form. On the other hand, it has the effect of “softening” and thus blunting the militant agency of a defiant black collective conscience and consciousness.